Hyper-tuned convolutional neural network based pediatric skeletal bone age estimation model - Sharma, Anubhav; Singh, Yeshpal; Kaur, Gagandeep (International Journal of Research in Medical Sciences, 2026)
Background: The pediatric skeletal bone age estimation model is developed to estimate the bone age in order to investigate the genetic and growth disorders of children’s. In this paper, a deep learning-based is presented for it. Method: Initially, in this model, the standard RSNA dataset of hand X-ray images is read. Followed by median filtering to remove noise and segmentation of the hand bone region using k-mean clustering. After that, the Convolutional Neural Network (CNN) algorithm is used to estimate the bone age. In this article, the CNN algorithm is used over other deep learning algorithms due to its automatically extracting the features from the hand X-ray images and estimating the bone age. Furthermore, in this research, the hyper-parameter optimization of the CNN algorithm is done by finding the best parameter values using the metaheuristic algorithm to enhance the performance of it. The metaheuristic walrus optimization algorithm is used, and it determines the general hyperparameters, such as the learning rate of the CNN algorithm, based on the objective function. Results: The simulation evaluation was done on MATLAB 2018b software. The standard RSNA dataset of hand X-ray images was used. The performance evaluation is done by splitting the same dataset into training and testing ratios and evaluated using the error metrics. The result indicates that the proposed model accomplishes the lower values of these error metrics over the previous approaches. Conclusion: The proposed method efficiently measures pediatric skeletal bone age by processing hand X-ray images with the CNN algorithm, which has been optimized through hyperparameter tuning.